The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1464420720986591
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and flammability evaluation of a new bio-based polyurethane foam with alumina trihydrate

Abstract: Flexural and flammability evaluation of a new bio-based polyurethane foam (PUF) with alumina trihydrate (ATH) added as flame retardant were carried out. The PUF was obtained from a blend of vegetable oils. Flexural behavior of the polyurethane with different mass fractions of flame retardant (ATH) was investigated according to ASTM D790-17. Flammability tests were performed according to ASTM D3801-20 and ASTM D635-14 for the vertical and horizontal positions, respectively. The ATH addition influenced the flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…According to their research, the PUF would suffer if ATH was added to the mixture in amounts greater than 40% due to particle saturation. Unlike [38], the epoxy resin in the current study has shown a saturation of 50% of the ATH and, hence the flexural modulus continuously increases until 50% addition of the ATH to the mixture. 13, and Figure 14 show the effect of the mass fraction and size of ATH loads respectively on the flexural modulus, flexural strength and maximum strain of the epoxy resin mixture, respectively.…”
Section: Flexural Propertiesmentioning
confidence: 75%
See 1 more Smart Citation
“…According to their research, the PUF would suffer if ATH was added to the mixture in amounts greater than 40% due to particle saturation. Unlike [38], the epoxy resin in the current study has shown a saturation of 50% of the ATH and, hence the flexural modulus continuously increases until 50% addition of the ATH to the mixture. 13, and Figure 14 show the effect of the mass fraction and size of ATH loads respectively on the flexural modulus, flexural strength and maximum strain of the epoxy resin mixture, respectively.…”
Section: Flexural Propertiesmentioning
confidence: 75%
“…The impact of the ATH fillers on the flexural characteristics of blocks made of polyurethane foam PUF was investigated by Silva et al [38]. They experimented with ATH content ranging from 10% to 50%.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…33 Therefore, more recently, it was investigated the influence of ATH mass fractions on the flexural behavior and flammability of a bio-based PUF, which was obtained from a blend of vegetable oils. 30 In order to complement the previous study, in the present work, it is evaluated the influence of ATH mass fractions on the compression behavior of the same PUF, as well as the morphology of its cell walls. All of that seeking to assure that the incorporation of ATH inside the PUF would not just increase its fire resistance, therefore, saving lives and money, but also improving its compression properties and amplifying its range of application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ATH-PUF mass fractions over 40% have shown good fire extinguishment properties and slower fire propagation in different flammability tests. 30,31 The PUF combustion process produces a considerable number of toxic materials, such as CO, HCN and smoke, therefore, reducing the flammability of the PUF means preventing the emission of these poisonous materials in the air, which would end up saving several human lives. 32 With the addition of flame retardant inside the PUF matrix, several properties of the foam might be affected.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of scientific publications regarding the lifespan of PUFs where their mechanical properties are relevant, such as sandwich panels [ 6 ]. Many studies regarding the synthesis, characterizations and applications of bio-based PUFs are being carried out every year due to its pairing characteristics with oil-based foams as well as its relative low cost and eco-friendly origin [ 7 , 8 , 9 , 10 ]. PUF is a two-phase material composed of a continuous polymer matrix and the gas in the discretely distributed cells.…”
Section: Introductionmentioning
confidence: 99%